Afrikaleidoskop meets ARTE - Yes we can (Afrikaleidoskop meets ARTE, 2024)
"AfriKaleidoscope" - the film program of the Cluster of Excellence at the University of Bayreuth - showed a film in cooperation with ARTE for the second time. On 14 June 2023, the Cluster presented a film premiere. "YES WE CAN – die neue Schwarze Malerei" is a documentary film by Marion Schmidt that deals with the so-called "Obama effect" and, among other things, explores the question of whether the official portraits of the presidential couple, which were painted by African-American artists and generated a great response, were the beginning of a new era or merely the trigger of a short-lived hype. The portraits ensured that the focus is currently on a new generation of African American artists whose works are being noticed in the marketplace. The "Obama effect," however, is not limited to the United States. Throughout the Western world, attention to the diverse and powerful, predominantly figurative paintings of Black artists* has increased significantly. As part of her film project, filmmaker Marion Schmidt visited three of them in their studios: Jerrell Gibbs from Baltimore, whose portraits paint primarily against the common clichés of Black men; Peter Uka, who is in Cologne pursuing his memories of his Nigerian homeland; and Shannon T. Lewis, whose works explore what the experience of migration means, a topic that the artist knows from her own experience. In addition, the filmmaker met an important representative of the new generation of Black artists in London: the painter Michael Armitage. The son of a Kenyan mother and a British father, he grew up with Kenyan art. Although what Armitage relates in his paintings is invariably set in East Africa, he has also studied the greats of the European art canon in depth. Following the exclusive premiere screening of the documentary, scholars* from the University of Bayreuth discussed her film and the motivation behind her project with filmmaker Marion Schmidt. The discussion focused, among other things, on the questions that the film also pursues: Is the art of the African diaspora perceived differently today than it was a few years ago? Is the Obama effect also being felt in Africa or Germany, and what developments are there in terms of reception and appreciation of Black art?